2013
DOI: 10.1186/1472-6882-13-214
|View full text |Cite
|
Sign up to set email alerts
|

Ssanghwa-tang, an oriental herbal cocktail, exerts anti-melanogenic activity by suppression of the p38 MAPK and PKA signaling pathways in B16F10 cells

Abstract: BackgroundSsanghwa-tang (SHT) is a widely used medication for the treatment of fatigue, pain, inflammation, hypothermia, erectile dysfunction, cancer, and osteoporosis in Asia, however, role of SHT on the melanin synthesis has not been checked previously. Thus, the present study was designed to determine the effect of SHT on α-melanocyte stimulating hormone (α-MSH)-induced melanogensis and its mechanisms of action in murine B16F10 melanoma cells.MethodCellular melanin content and tyrosinase activity in murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The MITF gene itself is a target of cAMP signaling induced by α-MSH, and predominantly regulates tyrosinase and TRP-1 protein expression [35,36,37]. In the cAMP-dependent signaling pathway, the dual phosphorylation of the cAMP response element binding protein (CREB), mediated by the kinase activities of ribosomal S6 kinase (RSK) and PKA, has been found to activate MITF transcription [38,39]. Furthermore, it has been reported that suppression of the cAMP-dependent signaling pathway causes MITF degradation in α-MSH-stimulated melanoma cells [40].…”
Section: Resultsmentioning
confidence: 99%
“…The MITF gene itself is a target of cAMP signaling induced by α-MSH, and predominantly regulates tyrosinase and TRP-1 protein expression [35,36,37]. In the cAMP-dependent signaling pathway, the dual phosphorylation of the cAMP response element binding protein (CREB), mediated by the kinase activities of ribosomal S6 kinase (RSK) and PKA, has been found to activate MITF transcription [38,39]. Furthermore, it has been reported that suppression of the cAMP-dependent signaling pathway causes MITF degradation in α-MSH-stimulated melanoma cells [40].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have indicated that the active constituents of SFJDCs, such as resveratrol and other flavonoids, inhibit acute lung injury (ALI). In addition, the MAPK and NF-kB signaling pathways may be involved in ALI (32)(33)(34)(35)(36)(37)(38). NF-κB is a key factor in the inflammatory response and is involved in the release of inflammatory factors and development of ALI (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK family proteins, such as p38, ERK and JNK, play critical roles in melanogenesis [24]. Most studies reported that the p38 MAPK signaling pathway activates MITF, which can up-regulate the expression of melanogenic enzymes [25].…”
Section: Discussionmentioning
confidence: 99%